Optimal control of discrete and differential inclusions with distributed parameters in the gradient form - E. N., Mahmudov; M. E., Unal (Springer Science and Business Media LLC, 2012)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Boundary value problems for functional-differential equations; first-order differential; Numerical methods for mathematical programming, optimization and variational techniques; square domain; duality theorems; Optimality conditions for problems involving partial differential equations; partial differential inclusions; Duality theory (optimization); discrete-approximation problem